2000
DOI: 10.5032/jae.2000.04051
|View full text |Cite
|
Sign up to set email alerts
|

The Move to Agriscience and Its Impact on Teacher Education in Agriculture

Abstract: Since the 1988 publication of Understanding Agriculture: New Directions for Education by the National Research Council, agricultural educators have experienced increased pressure to incorporate more science-based instruction. Recent research has examined where and how integration is occurring (Conroy, 2000; Johnson, 1996; Thompson, 1998). This qualitative study looks at the perceptions of agricultural educators and others regarding this shift in focus of instruction, and what implications exist for teacher edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 14 publications
1
26
0
Order By: Relevance
“…This implies a parallel between agriculture and vocational training which can be defined as a program where students are being prepared for a defined role (Kerka, 1997). A study by Shelley-Tolbert, Conroy, and Dailey (2000), albeit for secondary education in the United States, described the shift from skills-based training in agriculture to a greater emphasis on knowledge and understanding. This change was concomitant with an altered perception of the discipline to being regarded to have more scientific rigour.…”
Section: Discussionmentioning
confidence: 99%
“…This implies a parallel between agriculture and vocational training which can be defined as a program where students are being prepared for a defined role (Kerka, 1997). A study by Shelley-Tolbert, Conroy, and Dailey (2000), albeit for secondary education in the United States, described the shift from skills-based training in agriculture to a greater emphasis on knowledge and understanding. This change was concomitant with an altered perception of the discipline to being regarded to have more scientific rigour.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers (Balschweid, 2001;Conroy, et al, 1999;Shelley-Tolbert et al, 2000) have concluded that students should be provided sufficient context for what they are learning. It is believed that contextual learning is the key for improving a student's ability to synthesize information from numerous sources, to increase understanding of new and often contradictory information, for assisting in making meaning, and for enhancing the ability of students to think critically and transfer their learning to reallife experiences.…”
Section: Achievementmentioning
confidence: 99%
“…Assessments of student science achievement often shows performance levels below the degree of scientific literacy demanded in the workplace or in our society (Frome, 2001;National Assessment Governing Board, 2000). Researchers have explained this phenomenon by suggesting that the science being taught in schools today is too abstract, lacks real world connection and relevant context for students to apply the science learned in school to the real world (Conroy, Trumbull, & Johnson, 1999;Shelley-Tolbert, Conroy, & Dailey, 2000).…”
Section: Achievementmentioning
confidence: 99%
“…Contextual learning emphasizes higher-level thinking, knowledge transfer across academic disciplines, and collecting, analyzing and synthesizing information and data from multiple sources and viewpoints (Smith, 2000). Contextual learning facilitates learning in which students employ their academic understanding and abilities in a variety of out-of-school contexts to solve complex, real-world problems, both alone and in various groups (Shelley-Tolbert et al, 2000). Applying the context-based approach to learning was also found to be effective for engineering students who learn how to analyse experimental data, in the context of the laboratory, rather than learning data analysis skills in a non-contextual form such as in a mathematic-based course (Kukliansky & Eshach, 2014).…”
Section: Introductionmentioning
confidence: 99%